Ludwig von Mises jako krytyk autorytaryzmu i totalitaryzmu - Machaj, Mateusz; Turowski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Ludwig von Mises, a prominent representative of the Austrian school, was also a radical critic of authoritarianism and totalitarianism. His criticism was deeply rooted in economic theory, particularly in his authoritative comparative analysis of socialism and capitalism and his original theory of bureaucracy. At the same time, while emphasizing the economic aspects, he ignored the distinction between the two systems, treating any major appropriation of economic power by the state as a fast track to full political and economic control. Reconstructing Mises reasoning, the article discusses in turn the fundamental issues related to the analysis of the socialist order and its relation to authoritarian orders, supplemented by considerations of bureaucracy and war, as well as questions of the importance of democracy and the right to self-determination for the well-being of society.
Keywords: Mises, Ludwig von (1881-1973); szkoła austriacka; autorytaryzm; biurokracja; socjalizm